THE INFLUENCE OF PRODUCT QUALITY AND PROMOTION ON PURCHASE DECISIONS IN GIVETHANKS PRINTING IN MEDAN - Ginting, Samuel Tenang Ukur Ardianta; L.P. Sihombing, Thomas; Saragih, Heni Erfita (Jurnal Apresiasi Ekonomi, 2023)
ABSTRACTThe current needs of the community in various activities such as working in offices, doing business, college, and schools require an increasingly diverse range of paper printing products, consumers are looking for quality products through various forms of promotions from these paper printing companies, giving rise to business competition with introduce products according to the needs and desires of consumers, then communicate the advantages of these products. A consumer in making a buying decision is influenced by several factors including product quality and promotion. In the city of Medan there are several paper printing places, one of which is Givethank Printing, which has been around for 10 years, a paper printing company in the Jalan Jamin Ginting area of Medan, offering several types of products from paper printing such as banners, invitations, brochures, business cards, stamps, screen printing. , and others. This research is quantitative in nature, data collection was carried out by questionnaires with partial and simultaneous testing of product quality and promotion which had a positive and significant effect on purchasing decisions. The population and sample are customers of several communities and students residing in the area. The purpose of this study is to determine the effect of product quality and promotion on purchasing decisions at Givethanks Printing in Medan. The research methodology is quantitative, namely testing theories through measuring research variables with numbers and analyzing data using statistical procedures, with the help of the SPSS Software Application. This type of field research (field research) is research that is directly carried out in the field or on respondents. Keywords: Product Quality, Promotion, Purchase Decision